EFEKTIFITAS PENAMBAHAN SERBUK KUNYIT TERHADAP BILANGAN PEROKSIDA DAN BILANGAN ASAM MINYAK GORENG BEKAS PAKAI - Siti Mardiyah (UNUSA Press, 2018)
Used cooking oil is leftover cooking oil from food frying processes that have been used repeatedly. This resulted in increased high free radical and fatty acid content which can be harmful to health. One attempt to reduce oil damage is with the addition of antioxidants. Curcumin is an antioxidant contained in turmeric. Curcumin is an antioxidant phenol which have many double bonds that can capture free radicals, which can slow down the increase in the peroxide and acid number of used cooking oil. The purpose of this study was to determine the effect of turmeric powder on levels of acid number. This type of research is experimental by the number of samples in each treatment and as many as 16 samples. Formulation of the problem of this study is whether there is the effect of turmeric powder on levels of acid value on used cooking oil. The examination results on the levels of acid number of used cooking oil shows the average levels of the acid number of used cooking oil which without the provision of turmeric powder is as high as 0,641, while the one with the provision of turmeric powder is as high as 0,349. Statistical analysis by t test showed the effect of turmeric powder on levels of acid value on used cooking oil with value of p (sig) = 0.000 which is less than 0.05. Therefore, the turmeric powder can inhibit the decrease of acid number on used cooking oil so that the oil quality is maintained.